First Manifestation of Adult-Onset Still Disease After COVID-19 Vaccination: Two Cases - Monique K. van der Kooij; Hanna van Steenbergen; Yvonne Goekoop-Ruiterman; Darius Soonawala (Annals of Internal Medicine: Clinical Cases)
Adult Still disease (ASD) is a rare autoinflammatory condition of unknown cause. Viral or bacterial infections can trigger the onset of ASD. We describe the clinical features, treatment, and follow-up of 2 patients with new-onset ASD following COVID-19 vector vaccination. Our cases emphasize the importance of early diagnosis and lend weight to an association between COVID-19 vector vaccination and new-onset ASD.